2019
DOI: 10.1007/s11764-019-00801-w
|View full text |Cite
|
Sign up to set email alerts
|

Cancer specialist nurses’ perspectives of physical activity promotion and the potential role of physical activity apps in cancer care

Abstract: PurposeThe purpose of this study was to understand breast, prostate and colorectal cancer clinical nurse specialists’ (CNSs) perspectives on physical activity (PA) promotion and the role of smartphone apps to support PA promotion in cancer care.MethodsCNSs working in breast, prostate or colorectal cancer were recruited via advertisements distributed by professional organizations. In-depth semi-structured telephone interviews were conducted and analysed using thematic analysis.ResultsNineteen CNSs participated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 59 publications
0
66
0
2
Order By: Relevance
“…A mobile nursing app in nursing services is still in its infancy. Previous studies mainly focus on the construction of a mobile nursing app [9,10], the investigation of application needs [11,12] and the exploration of the feasibility of nursing [13][14][15]. A mobile nursing app has the characteristics by the use of mobile applications, such as the emphasis on the individual's smart phone use ability [16], and the ability to accept mobile applications [17], which puts forward higher requirements for nurses.…”
Section: Introductionmentioning
confidence: 99%
“…A mobile nursing app in nursing services is still in its infancy. Previous studies mainly focus on the construction of a mobile nursing app [9,10], the investigation of application needs [11,12] and the exploration of the feasibility of nursing [13][14][15]. A mobile nursing app has the characteristics by the use of mobile applications, such as the emphasis on the individual's smart phone use ability [16], and the ability to accept mobile applications [17], which puts forward higher requirements for nurses.…”
Section: Introductionmentioning
confidence: 99%
“…We also included components of the PBA to gain ongoing feedback from user perspectives to optimise future implementation. Furthermore, we addressed previously reported barriers to integrating NICE recommendations into practice [ 10 , 11 ], by developing an intervention to be delivered by community providers; to enhance patient accessibility and scalability during the implementation process [ 50 ]. Furthermore, NHS services are currently under extreme pressure due to the coronavirus pandemic [ 51 ] thus highlighting the need to explore new pathways of care.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the National Institute for Health and Care Excellence (NICE; NG131 1.4.19) include in the guidelines for locally advanced and advanced prostate cancer a recommendation that men on ADT should be offered supervised, aerobic and resistance exercise twice weekly for 12 weeks [ 8 ]. However, these recommendations are seldom integrated into practise [ 9 ] due to several reported barriers from healthcare professionals (HCPs), including a lack of exercise services to refer men to [ 10 ] and limited awareness of clinical exercise recommendations [ 11 ], thus adding to unmet needs reported by men with prostate cancer [ 12 ]. Furthermore, men on ADT who participated in a 12-month supervised exercise programme believe community gyms are easily accessible and a location they look forward to attending [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that ICU management led by intensive care physicians is associated with improvements in mortality and the duration of hospitalization in Japanese and international contexts [20,22]. Advanced practice nurses, including CNSs, have advanced nursing skills and clinical decision making experience in their area of expertise [23][24][25], which can facilitate positive outcomes by guiding the medical team to appropriate solutions [6,[26][27][28], especially for patients with complex and difficult problems in the ICU and general wards. In low-intensity ICUs or open ICUs, in which intensive care physicians do not determine treatment for various reasons, collaboration between physicians and the CNS responsible for advanced nursing practice improves treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%